Preparedness among Reserve Officers' Training Corps Graduates on the Rigors of ROTC and Defense Security: Basis for Policy Enhancement - Gantalao, Jilmar S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The Philippines Reserve Officers' Training Corps aims to provide military education and training for students to mobilize them for national defense preparedness. This study aimed to assess the rigor of the Philippine Reserve Officers' Training Corps, and defense and security preparedness among ROTC graduates in selected universities in the Philippines, and determined the significant difference in the perceived level of preparedness on the rigor of the Philippine RTOC among Military Science courses graduates in selected universities such as: physical organization of cadets, combat training of individual soldiers, regional annual administrative and tactical inspection, drill and ceremonies, infantry, rescue, field artillery, and; civil operation activities as assessed by the three groups of respondents. Moreover, the study also determined the significant difference in the perceived level of preparedness on defense and security such as: internal security operations, territorial defense, disaster response, international defense, security engagements, international humanitarian assistance, peacekeeping operations, and support to national development as assessed by the two (2) groups of respondents. This study utilized a descriptive correlational research design. The study covered 200 respondents; composed of 100 Military Science 42 Graduates, and 100 Military Science 43 graduates conducted during the School Year 2022 – 2023. Generally, the respondents were Highly Prepared for the rigor of the Reserved Officers Training Corps. On the other hand, the respondents were Highly Prepared on defense and security as embedded in the Reserved Officers Training Corps. Further studies may be conducted using empirical evidence to further the implementation of ROTC mandates, supplementation to an early career in AFP, and the impact of ROTC on both high school and college graduates in the Philippines.